Lag Screw Technique for Treating a Mandibular Angle Fracture: Case Report (International Journal of Medical and Surgical Sciences, 2014)
The treatment of mandibular angle fractures involves several postsurgical complications and is in greater demand when compared to therapeutic approaches for other types of mandibular fractures. Such postsurgical complications as bleeding, swelling, infection, dehiscence, pseudoarthrosis and paresthesia might affect individuals in both sexes and at all age groups. The presence of a mandibular third molar, a cross-sectional area thinner than the tooth-bearing region, and biomechanical forces might hamper the surgery, making it longer and more complex. Internal fixation is aimed at undisturbed healing under condition of functional and without any period of intermaxillary fixation. Adequate fixation depends on different fracture types, patients' general health and compliance, and the timing of the operation. This case report involves a mandibular angle fracture successfully treated with the lag screw technique, a simple approach to treat one of the most common fractures involving the mandible, quickly restoring the patient's oral functions.